Mexico : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper assesses the potential financial vulnerabilities of the corporate sector in Mexico. It provides an overview of salient features of the Mexican corporate sector. The paper also presents the formal stress tests that estimate the potential effects of some macroeconomic and financial shocks, such as a sharp depreciation of the exchange rate, a sustained increase in interest rates, a slowdown in demand, and a prolonged international market closure on the corporate sector.